Food democracy and sustainability in France and Chile: Community gardens promote ecological citizenship - Biskupovic, Consuelo; Maurines, Béatrice; Carmona, Rosario; Canteros, Eduardo (Frontiers in Sustainable Food Systems, 2022)
This study explored cases of sustainable food production in urban and non-urban areas, including the development of urban gardens, and particularly the social relations involved in these community projects. A qualitative approach was used to compare four case studies in Chile and France: shared gardens in Lyon, family and workers’ gardens in Santiago in Chile, an indigenous agricultural project in Lonquimay in the southern Andes, and the work of the NGO Cultivos Urbanos. The data was collected through surveys, participant observation and semi-structured in-depth interviews. The results show that tending gardens in these settings (worker, family, collective or shared gardens) promotes social values that can lead to more sustainable forms of community living. As opposed to intensive agriculture, small-scale gardening practices, specifically in urban and peri-urban gardens, encourage human/non-human relationships and the transmission of caring for nature and for others, which promotes ecological citizenship.